ANALYSIS OF THE PROBLEM OF TRAINING MOUNTAIN GUIDES IN UKRAINE TAKING INTO ACCOUNT THE FEATURES OF THE REGION (Physical Culture and Sport: Scientific Perspective, 2023)
The article examines the attitude of the mountain community to the training of mountain guides in Ukraine with the aim of introducing the training of mountain guides taking into account the wishes and needs of guides and clients. To develop this topic, a Google Forms survey was created. The first is for guides or instructors, the second is for athletes or clients. 21 people who take people to the mountains and 35 people who are users of these services took part in the survey during the month. The topics of training mountain guides and improving their qualifications were discussed. A survey was made which areas of guide training, in the opinion of both guides and clients, should be included in the program and what form of training should be and at what time. It was discussed whether there is a need for manuals on mountain sports and whether a unified register of mountain guides of Ukraine is needed. They also considered the promising directions for the development of mountain guide services. During the survey, it was found out that those who are currently taking people to the mountains have been engaged in mountain sports for a long time, but the skill level of the majority is not high. They discovered that such modules as mountaineering, rock climbing and tourism should be present in training. It is important to acquire both theoretical and practical knowledge, as well as have time for internships and take exams. From the client's point of view, it is important for guides to improve communication and organizational skills and this should also be in training. Therefore, the topic of training mountain guides is relevant and 81% of the surveyed guides believe that courses for instructors are needed and 100% want to improve their qualifications. In Ukraine, there is a need to create multi-level training courses for mountain guides. Those who are now "self-taught guides" have a desire to increase their skill level. There is a demand for the services of mountain guides and there are directions in which it is possible to develop. Therefore, it is possible to start developing a training program for mountain guides in Ukraine.
Keywords: Mountain guides; instructor; client; survey; training